Common Foot Fracture Patterns: A Descriptive Study on 558 Cases - Sayyed-Hadi Sayyed-Hosseinian; Mohammad Reza Sarshar; Mahdieh Parsaeian; Mohammad Hossein Ebrahimzadeh; Ali Birjandinejad (Journal of Orthopedic and Spine Trauma)
Background: Foot fractures are relatively common among trauma patients, and further research is needed to identify prevalent fracture patterns. This study aimed to explore common foot fracture patterns. Methods: This cross-sectional study included patients admitted to a trauma center between 2018 and 2020. All patients with acute foot injuries were identified using the hospital information system (HIS). Data such as age, sex, trauma mechanism, mobile injuries, hospitalization status, and whether the injury was open or closed were extracted from patient records. Radiographies were reviewed to evaluate the location of fractures or dislocations and their anatomical classification. Results: A total of 558 patients with an average age of 35.70 ± 16.55 years were studied, of whom 489 (67%) were men. The most common mechanism of trauma was motor vehicle accidents (240/558, 43.1%). The forefoot was the most frequently affected area (48.7%). Among the different bones, the calcaneus had the highest fracture incidence (233/558, 41.8%). There were 63 patients with dislocations, with Lisfranc dislocation being the most common (32/558, 50.8%). Calcaneus fractures were significantly more common in men than in women (P = 0.008), while fractures of the second (P = 0.010) and fifth (P = 0.011) metatarsals were significantly more common in women. Conclusion: Calcaneus fractures were most common, especially in men, while women had more metatarsal fractures. Motor vehicle accidents were the primary cause of trauma. The mechanism of injury plays a crucial role.